Analisis Penerapan PPN dan PPH Pasal 22 Atas Pengadaan Barang di Balai Jembatan Kementrian PUPR - Intan Damarwati; Gunardi Gunardi (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Tax is one of the main components of the Indonesian economy which serves as the source of the funding for APBD and APBN.The government treasurer as the functional official has the obligation and authority to deposit and report Value Added Tax (VAT) and Income TaxArticle 22 from every payment for the procurement of goods whose funding source is from the APBN. The purpose of this research is to find out the implementation of calculation, depositing, and reporting of VAT and Income Tax Article 22 for the procurement of goods at Balai Jembatan of the Ministry of Public Works and Public Housing.This study was conducted with the descriptive qualitative method fromDecember2021 to January 2022.The results of the research show that the VAT is calculated using a 10% rate, while the Income Tax Article 22 used a 1,5% rate, which is then deposited using the Persepsi payment code from Kantor Pos Indonesia. Reportings are done by using SPT Masa Unifikasi which needs to be done in 20 days maximum from the end of the tax period.Reporting, depositing, and calculation of VAT and Income Tax Article 22 by the treasurer of Balai Jembatanof the Ministry of Public Works and Public Housing have been carried out in accordance with the regulations regarding tax from the Ministry of Finance. However, there are still delays in reporting VAT and Income Tax Article 22 in several tax periods. Keywords: Government Treasurer, VAT, Income Tax Article 22